Effects of pH and sugar concentration in Zygosaccharomyces rouxii growth and time for spoilage in concentrated grape juice at isothermal and non-isothermal conditions - Rojo, Cecilia; Arroyo López, Francisco Noe; Lerena, María Cecilia; Mercado, Laura Analia; Torres, Adriana Mabel; Combina, Mariana (2018)
The effect of pH (1.7–3.2) and sugar concentration (64–68 °Brix) on the growth of Zygosaccharomyces rouxii MC9 using response surface methodology was studied. Experiments were carried out in concentrated grape juice inoculated with Z. rouxii at isothermal conditions (23 °C) for 60 days. pH was the variable with the highest effect on growth parameters (potential maximum growth rate and lag phase duration), although the effect of sugar concentration were also significant. In a second experiment, the time for spoilage by this microorganism in concentrated grape juice was evaluated at isothermal (23 °C) and non-isothermal conditions, in an effort to reproduce standard storage and overseas shipping temperature conditions, respectively. Results show that pH was again the environmental factor with the highest impact on delaying the spoilage of the product. Thereby, a pH value below 2.0 was enough to increase the shelf life of the product for more than 60 days in both isothermal and non-isothermal conditions. The information obtained in the present work could be used by producers and buyers to predict the growth and time for spoilage of Z. rouxii in concentrated grape juice.